MORPHOLOGICAL AND SYNTACTIC FEATURES OF SENTENCES IN THE UZBEK LANGUAGE (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Morphological and syntactic features of sentences in Uzbek have an important place in linguistics. Morphology studies the structure of words, their formation and grammatical features, while syntax studies how words are related to each other and the structure of sentences. This article provides detailed information about the morphological and syntactic features of sentences in the Uzbek language.